Penyaringan dengan Variasi Media Filter untuk Menurunkan Mangan pada Air Sumur Gali - Yeni Yuliani; Lilik Hendrarini; Haryono Haryono (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Water is essential for life and it should meet the quality and quantity requirements. High level contamination of toxic contaminants in drinking water for a long time can be harmful for human health. Manganese is one of dissolved metal that can contaminate drinking water. The syndrome known as “manganism” and it is caused by exposure to very high levels of manganese and is characterized by a “Parkinson-like syndrome”. The purpose of this study was to determine the effect of various filter media on Manganese concentration in well water. This study was quasi ex-periment with Pre Test-Post Test design. The study was conducted on September to December 2018. Object of the study was well water in Dusun Kauman Tamanan Banguntapan Bantul. The study used four kind of filters. i.e. resin filter, zeolite filter, activated carbon filter, and combined filter. There were six pre test samples and 24 post test samples. The data were analyzed using paired t-test and One Way Anova in SPSS program. The study showed significant difference between the level of Manganese before and after treatment. The ability of resin, zeolite, activa-ted carbon, and combined filter to reduce Manganese were 92,32%, 57,11%, 73,49%, and >98,90% respectively. Combined filter gave the best performance on reducing Manganese. How-ever One Way Anova test showed there’s no significant difference between groups.